Answer:
69 students attend the camp
Step-by-step explanation:
8% of 75 = 6
75 - 6 = 69
Answer:
![\int\frac{x^{4}}{x^{4} -1}dx = x + \frac{1}{4} ln(x-1) - \frac{1}{4} ln(x+1)-\frac{1}{2} arctanx + c](https://tex.z-dn.net/?f=%5Cint%5Cfrac%7Bx%5E%7B4%7D%7D%7Bx%5E%7B4%7D%20-1%7Ddx%20%3D%20x%20%2B%20%5Cfrac%7B1%7D%7B4%7D%20ln%28x-1%29%20-%20%5Cfrac%7B1%7D%7B4%7D%20ln%28x%2B1%29-%5Cfrac%7B1%7D%7B2%7D%20arctanx%20%2B%20c)
Step-by-step explanation:
![\int\frac{x^{4}}{x^{4} -1}dx](https://tex.z-dn.net/?f=%5Cint%5Cfrac%7Bx%5E%7B4%7D%7D%7Bx%5E%7B4%7D%20-1%7Ddx)
Adding and Subtracting 1 to the Numerator
![\int\frac{x^{4} - 1 + 1}{x^{4} -1}dx](https://tex.z-dn.net/?f=%5Cint%5Cfrac%7Bx%5E%7B4%7D%20-%201%20%2B%201%7D%7Bx%5E%7B4%7D%20-1%7Ddx)
Dividing Numerator seperately by ![x^{4} - 1](https://tex.z-dn.net/?f=x%5E%7B4%7D%20-%201)
![\int 1 + \frac{1}{x^{4}-1 }\, dx](https://tex.z-dn.net/?f=%5Cint%201%20%2B%20%5Cfrac%7B1%7D%7Bx%5E%7B4%7D-1%20%7D%5C%2C%20dx)
Here integral of 1 is x +c1 (where c1 is constant of integration
----------------------------------(1)
We apply method of partial fractions to perform the integral
=
------------------------------------------(2)
![\frac{1}{(x-1)(x+1)(x^{2}+1)} = \frac{A(x+1)(x^{2} +1) + B(x-1)(x^{2} +1) + C(x-1)(x+1)}{(x-1)(x+1)(x^{2} +1)}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%28x-1%29%28x%2B1%29%28x%5E%7B2%7D%2B1%29%7D%20%3D%20%5Cfrac%7BA%28x%2B1%29%28x%5E%7B2%7D%20%2B1%29%20%2B%20B%28x-1%29%28x%5E%7B2%7D%20%2B1%29%20%2B%20C%28x-1%29%28x%2B1%29%7D%7B%28x-1%29%28x%2B1%29%28x%5E%7B2%7D%20%2B1%29%7D)
1 =
-------------------------(3)
Substitute x= 1 , -1 , i in equation (3)
1 = A(1+1)(1+1)
A = ![\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D)
1 = B(-1-1)(1+1)
B = ![-\frac{1}{4}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B4%7D)
1 = C(i-1)(i+1)
C = ![-\frac{1}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B2%7D)
Substituting A, B, C in equation (2)
= ![\int\frac{1}{4(x-1)} - \frac{1}{4(x+1)} -\frac{1}{2(x^{2}+1) }](https://tex.z-dn.net/?f=%5Cint%5Cfrac%7B1%7D%7B4%28x-1%29%7D%20-%20%5Cfrac%7B1%7D%7B4%28x%2B1%29%7D%20-%5Cfrac%7B1%7D%7B2%28x%5E%7B2%7D%2B1%29%20%7D)
On integration
Here ![\int \frac{1}{x}dx = lnx and \int\frac{1}{x^{2}+1 } dx = arctanx](https://tex.z-dn.net/?f=%5Cint%20%5Cfrac%7B1%7D%7Bx%7Ddx%20%3D%20lnx%20and%20%5Cint%5Cfrac%7B1%7D%7Bx%5E%7B2%7D%2B1%20%7D%20dx%20%3D%20arctanx)
=
-
-
+ c2---------------------------------------(4)
Substitute equation (4) back in equation (1) we get
![x + c1 + \frac{1}{4} ln(x-1) - \frac{1}{4} ln(x+1) - \frac{1}{2} arctanx + c2](https://tex.z-dn.net/?f=x%20%2B%20c1%20%2B%20%5Cfrac%7B1%7D%7B4%7D%20ln%28x-1%29%20-%20%5Cfrac%7B1%7D%7B4%7D%20ln%28x%2B1%29%20-%20%5Cfrac%7B1%7D%7B2%7D%20arctanx%20%2B%20c2)
Here c1 + c2 can be added to another and written as c
Therefore,
![\int\frac{x^{4}}{x^{4} -1}dx = x + \frac{1}{4} ln(x-1) - \frac{1}{4} ln(x+1)-\frac{1}{2} arctanx + c](https://tex.z-dn.net/?f=%5Cint%5Cfrac%7Bx%5E%7B4%7D%7D%7Bx%5E%7B4%7D%20-1%7Ddx%20%3D%20x%20%2B%20%5Cfrac%7B1%7D%7B4%7D%20ln%28x-1%29%20-%20%5Cfrac%7B1%7D%7B4%7D%20ln%28x%2B1%29-%5Cfrac%7B1%7D%7B2%7D%20arctanx%20%2B%20c)
Answer: This is an reduction.
Step-by-step explanation:
- A dilation a king of transformation that creates an similar image (about a center of dilation) of the actual figure by changing its size with the use of a scale factor(k).
- It either shrinks or stretches the image.
- If |k| is greater than 1 then the image is an enlargement .
- If |k| is less than 1 then the image is an reduction.
- If |k| is equals to 1 then there is no change in size.
Given : A street is drawn by dilating segment
about center A with a scale factor greater than 0 but less than 1.
Then by using (2.) , we can say that this is an reduction.